Discoursal Value of Transferring Prepositions in the Holy Quran into English - Khalaf , Meethaq Khamees (International Journal of Psychosocial Rehabilitation, 2020)
The study examines the discoursal value of interlingual transference of prepositions as rhetorical devices in the Holy Quran. It aims to investigate the adequacy and accuracy of translating selected prepositions from the Holy Quran into English identified by the culture of an Arab-Muslim translator and a non-Arab non- Muslim one. To achieve this objective, the study adopts the qualitative phase of research since the prepositions in verses selected from the Holy Quran are not the only ones but there are many other examples. The findings of the study show that the discoursal value of transferring the selected prepositions is restricted by the cultural and religious background of translator. Also the study reveals that there are different meanings of transferred selected prepositions. Palmer as a non-Arab non-Muslim translator misses some shades of meaning of prepositions when he translates them into English which are accurately and successfully translated by an Arab Muslim translator Ghali.